Longitudinal distribution of Copepoda populations in the transition zone of Paranapanema River and Jurumirim Reservoir (São Paulo, Brazil) and interchange with two lateral lakes. - Casanova, S. M.; Henry, R. (FapUNIFESP (SciELO), 2004)
Longitudinal changes in composition, abundance, and distribution of copepods were studied at the transition zone of Paranapanema River-Jurumirim Reservoir (SP, Brazil). The interchange of biotic material between marginal lakes and the river system was also examined. Water samples were obtained from 6 stations along a stretch of 13 km of the Paranapanema River, from an upstream reach with high water velocity up to the river mouth into Jurumirim Reservoir. Two other sites in lateral lakes were also sampled. Nine copepod taxa were identified: 3 calanoids (Argyrodiaptomus furcatus Sars, Notodiaptomus iheringi Wright, and N. conifer Sars) and 6 cyclopoids (Eucyclops Claus, Microcyclops Claus, Mesocyclops longisetus Thiébaud, Thermocyclops decipiens Fischer, T. minutus Lowndes, and Paracyclops Claus). Harpacticoids were also collected. Calanoid and cyclopoid nauplii and copepodids, and harpacticoids were the most abundant organisms. In general, there was a longitudinal decrease in copepod abundance, whereas an increase was detected near the lakes. The abundance of most copepods was inversely correlated with current velocity and suspended solids. Higher abundance was observed in the river main course during the rainy season, during which there is a higher connectivity between the lakes and the main river. This promotes exportation of biologic material from marginal lakes to the river system, a biotic exchange reflecting the importance of marginal lakes to the river community structure.
Keywords: animal; Brazil; classification; copepod; ecosystem; population density; population dynamics; river; season; water flow; Animals; Copepoda; Ecosystem; Population Density; Population Dynamics; Rivers; Seasons; Water Movements